2018
DOI: 10.1093/annonc/mdy201
|View full text |Cite
|
Sign up to set email alerts
|

nab-Paclitaxel plus carboplatin or gemcitabine versus gemcitabine plus carboplatin as first-line treatment of patients with triple-negative metastatic breast cancer: results from the tnAcity trial

Abstract: BackgroundMetastatic triple-negative breast cancer (mTNBC) has a poor prognosis and aggressive clinical course. tnAcity evaluated the efficacy and safety of first-line nab-paclitaxel plus carboplatin (nab-P/C), nab-paclitaxel plus gemcitabine (nab-P/G), and gemcitabine plus carboplatin (G/C) in patients with mTNBC.Patients and methodsPatients with pathologically confirmed mTNBC and no prior chemotherapy for metastatic BC received (1 : 1 : 1) nab-P 125 mg/m2 plus C AUC 2, nab-P 125 mg/m2 plus G 1000 mg/m2, or G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 23 publications
0
73
0
4
Order By: Relevance
“…The NCCN panel had included combination chemotherapy regimens as useful in certain circumstances. The combination regimen options include doxorubicin/ cyclophosphamide (AC) 154,155 ; epirubicin/cyclophosphamide (EC) 156 ; docetaxel and capecitabine 121 ; gemcitabine and paclitaxel (GT) 157 ; cyclophosphamide/methotrexate/ fluorouracil (CMF) 158 ; gemcitabine/carboplatin [159][160][161] ; carboplatin with paclitaxel or albumin-bound paclitaxel [162][163][164] ; and paclitaxel/bevacizumab. [165][166][167] For the doublet regimens that are included, randomized phase III trials have shown that the ORR with first-line AC treatment ranges from 47% to 54% and OS is around 20 months.…”
Section: Preferred Chemotherapy Regimens For Stage IV or Recurrent Mementioning
confidence: 99%
See 2 more Smart Citations
“…The NCCN panel had included combination chemotherapy regimens as useful in certain circumstances. The combination regimen options include doxorubicin/ cyclophosphamide (AC) 154,155 ; epirubicin/cyclophosphamide (EC) 156 ; docetaxel and capecitabine 121 ; gemcitabine and paclitaxel (GT) 157 ; cyclophosphamide/methotrexate/ fluorouracil (CMF) 158 ; gemcitabine/carboplatin [159][160][161] ; carboplatin with paclitaxel or albumin-bound paclitaxel [162][163][164] ; and paclitaxel/bevacizumab. [165][166][167] For the doublet regimens that are included, randomized phase III trials have shown that the ORR with first-line AC treatment ranges from 47% to 54% and OS is around 20 months.…”
Section: Preferred Chemotherapy Regimens For Stage IV or Recurrent Mementioning
confidence: 99%
“…163,164 The randomized trial, tnAcity, evaluated the efficacy and safety of first-line albumin-bound paclitaxel plus carboplatin, albumin-bound paclitaxel plus gemcitabine, and gemcitabine plus carboplatin in patients with metastatic triple-negative breast cancer. 162 The results of this trial reported that median PFS was significantly longer with albumin-bound paclitaxel plus carboplatin versus albumin-bound paclitaxel/gemcitabine (8.3 vs 5.5 months; HR, 0.59; 95% CI, 0.38-0.92; P5.02) or gemcitabine/carboplatin (8.3 vs 6.0 months; HR, 0.58; 95% CI, 0.37-0.90; P5.02). The median OS was also longer with albumin-bound paclitaxel plus carboplatin versus albumin-bound paclitaxel/gemcitabine (16.8 vs 12.1 months; HR, 0.73; 95% CI, 0.47-1.13; P5.16) or gemcitabine/carboplatin (16.8 vs 12.6 months; HR, 0.80; 95% CI, 0.52-1.22; P5.29).…”
Section: Preferred Chemotherapy Regimens For Stage IV or Recurrent Mementioning
confidence: 99%
See 1 more Smart Citation
“…Determining the role of single-agent platinum salts has been challenging, while synergistic combinations have shown far more encouraging results in advanced TNBC. The phase 2 tnAcity trial suggested a solid rationale for the nab-paclitaxel/carboplatin doublet as first-line treatment in unselected TNBC patients, with a 73% response rate and improved PFS versus the nab-paclitaxel /gemcitabine (median PFS 8.3 vs 5.5 months; HR 0.59 [95% CI, 0.38-0.92]; p = 0.02) and gemcitabine/carboplatin combinations (median PFS 8.3 vs 6.0 months; HR 0.58 [95% CI, 0.37-0.90]; p = 0.02) [4].…”
Section: The Unselected Tnbc Population: Looking For the Pearl In Thementioning
confidence: 99%
“…для группы терапии гемцитабин + карбоплатин (ОР-0,58, р = 0,02). Показатели общей выживаемости были также выше в группе наб-паклитаксела с карбоплатином, однако статистически значимой разницы не достигнуто [24].…”
Section: применение набпаклитаксела в терапии метастатического рмжunclassified